Aghayeva, Konul - (:unkn) unknown (My University, 2026)
Konul Asaf Aghayeva graduated from the Azerbaijan State University of Economics with a Bachelor’s degree in Management of Production Systems in 1998 and a Master’s degree in the same field in 2000. She began her professional career in 1994 at Baku Engineering Construction Trust No. 34, where she worked as a Site Engineer and later as Deputy Head. Since 2000, she has been working at the Azerbaijan University of Architecture and Construction (AzUAC), where she has held academic positions from Assistant Lecturer to Senior Lecturer. Since 2022, she has been an Associate Professor at the Department of Economic Theory and Marketing. Since March 2023, she has also served as Director of the Quality Assurance and Monitoring Center at AzUAC. In 2005, she was awarded the degree of Doctor of Philosophy (PhD) in Economics after defending her dissertation, Prospective Directions for the Development of Private Housing Construction in Azerbaijan. She attained the academic title of Associate Professor in 2010. Her research interests include economics, higher education quality assurance, strategic management, sustainable development, and construction economics. She is the author of 2 monographs, 3 textbooks, 5 teaching manuals, 4 methodological manuals, and more than 120 scientific and methodological publications, including 14 articles in internationally recognized impact-factor journals.